Agricultural development strategies and southeastern Anatolia project regional development activities in the GAP region - Baysan N. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
GAP is the largest regional development project in Turkey, and also one of the major projects in the world. The GAP project area lies in southeastern Turkey, covering the eight provinces of Adiyaman, Batman, Diyarbakir, Gaziantep, Mardin, Kilis, Sanliurfa and Sirnak. The population of the region in the 1997 census was 6,152,000, of which 35.93 per cent was urban. There are 13 projects in the lower Firat and Dicle basins that consists of dam hydropower plants and irrigation schemes and accompanying growth of agriculture, transportation, industry, telecommunications, health and education sectors and services in the region. The GAP area is bigger than Holland, Denmark, Belgium, Ireland and Luxembourg.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)